1987
DOI: 10.1136/vr.120.26.615
|View full text |Cite
|
Sign up to set email alerts
|

Cryptosporidium in market pigs in southern California, USA

Abstract: Faecal specimens from 200 market swine (115 feeder pigs and 85 butcher hogs) offered for sale at a southern California livestock auction yard during a three-month period, were examined for cryptosporidium oocysts. Of the 10 pigs (5 per cent) found to be excreting the parasite, seven were feeder pigs and three were butcher hogs. Of the feeder pigs four (4.1 per cent) came from the 98 non-diarrhoeic pigs and three (17.6 per cent) from 17 diarrhoeic pigs. The 85 butcher hogs were all apparently healthy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…The results of this study revealed high prevalence (30%) of Cryptosporidium infection in slaughtered finishers (5.5-6 months old), whereas a much lower prevalence (5-12%) has been detected in pigs of the same age category by Tacal et al (1987), Suárez-Luengas et al (2007), and Zintl et al (2007). Similar results were published by Quílez et al (1996), who found Cryptosporidium in 34% of 2-6 month old fattening pigs.…”
Section: Discussionsupporting
confidence: 79%
“…The results of this study revealed high prevalence (30%) of Cryptosporidium infection in slaughtered finishers (5.5-6 months old), whereas a much lower prevalence (5-12%) has been detected in pigs of the same age category by Tacal et al (1987), Suárez-Luengas et al (2007), and Zintl et al (2007). Similar results were published by Quílez et al (1996), who found Cryptosporidium in 34% of 2-6 month old fattening pigs.…”
Section: Discussionsupporting
confidence: 79%
“…A high rate of prevalence ranging from 62.4% to 71.7% has occasionally been reported in adult cattle (Lorenzo-Lorenzo et al 1993;Scott et al 1995), and infection has also been described in mature pigs (Tacal et al 1987). In an epidemiology survey previously carried out in Aragón (Quílez et al, unpublished data), we found that 17.8% of cows were infected, whereas none of the sows was shedding C. parvum oocysts.…”
Section: Ifa Titermentioning
confidence: 76%
“…In sheep, Cryptosporidium ubiquitum, Cryptosporidium xiaoi and C. parvum have been reported relatively frequently, whereas for goats, species and genotypes of Cryptosporidium are not comprehensively documented (Santín, 2013). Cryptosporidiosis and giardiasis in pigs and horses are often asymptomatic, even though there were some reports of disease in very young animals (Hamnes et al, 2007;Rotkiewicz et al, 2001;Tacal et al, 1987;Xiao and Herd, 1994).…”
Section: Brief Account Of Cryptosporidium and Giardia Of Humansmentioning
confidence: 99%